FRESH SEMEN MOTILITY OF ETAWA CROSSBREED (PE) WITH DIFFERENT TIME STORAGE AND TEMPERATURE USING VARIOUS DILUENT - Sudarsono, Enike Dwi Kusumawati, Aju Tjatur Nugroho Krisnaningsih (Jurnal Sains Peternakan, 2016)
The purpose of this research is to knowing fresh semen motility of etawa crossbreed (PE) with time storage and temperature using various diluent. The methods is a reseach laboratory using a completely randomized design (CRD) factorial. The diluent treatments are Egg Yolk Tris Aminomethane, Cauda Epididymal Plasma, Ringer, and coconut water. The time storages are 0 hours, 1 hours, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, and each treatment replicated 10 times. The results showed that the fresh semen motility of crossbreed Etawa (PE) with different time storage and temperature using various diluents is a very significally influence (P